Digitalisasi Pemasaran Kain Tenun Desa Kalena Wanno: Pengembangan Sistem Informasi Berbasis Web - Marselina Anjela Bangnga; Ardiyanto Dapadeda; Felysitas Ema Ose Sanga (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2026)
Sumba woven fabrics have developed into a global market commodity sought after by collectors and tourists. However, artisans in Kalena Wanno Village still face limitations in traditional marketing channels. This study aims to develop a website as a means of promotion and sales to expand market access and improve the welfare of local artisans through technology use. The research method used is descriptive qualitative with a Waterfall model system development approach. The results show that the application of the "Tenun Kalena Wanno" website has successfully provided broader promotion and transactions through a public catalog feature accessible without time and geographical restrictions. This website effectively connects artisans directly with consumers, thereby strengthening the economic independence of the village community through digitization of cultural heritage. The system supports transparent pricing and eliminates intermediary chains, allowing artisans to gain direct financial benefits.